REFRACTORY THROMBOCYTOPENIA AND NEUTROPENIA: A DIAGNOSTIC CHALLENGE - Emmanuel Gyan; François Dreyfus; Pierre Fenaux (Mediterranean Journal of Hematology and Infectious Diseases)
Background. The 2008 WHO classification identified refractory cytopenia with unilineage dysplasia (RCUD) as a composite entity encompassing refractory anemia, refractory thrombocytopenia (RT), and refractory neutropenia (RN), characterized by 10% or more dysplastic cells in the bone marrow respective lineage. The diagnosis of RT and RN is complicated by several factors.  Diagnosing RT first requires exclusion of familial thrombocytopenia, chronic auto-immune thrombocytopenia, concomitant medications, viral infections, or hypersplenism. Diagnosis of RN should also be made after ruling out differential diagnoses such as ethnic or familial neutropenia, as well as acquired, drug-induced, infection-related or malignancy-related neutropenia. An accurate quantification of dysplasia should be performed in order to distinguish RT or RN from the provisional entity named idiopathic cytopenia of unknown significance (ICUS). Cytogenetic analysis, and possibly in the future somatic mutation analysis (of genes most frequently mutated in MDS), and flow cytometry analysis aberrant antigen expression on myeloid cells may help in this differential diagnosis. Importantly, we and others found that, while isolated neutropenia and thrombocytopenia are not rare in MDS, those patients can generally be classified (according to WHO 2008 classification) as refractory cytopenia with multilineage dysplasia or refractory anemia with excess blasts, while RT and RN (according to WHO 2008) are quite rare.These results suggest in particular that identification of RT and RN as distinct entities could be reconsidered in future WHO classification updates.